Beef value chain in Northern Laos (Luang Prabang, Luang Namtha and Xiengkhouang Provinces) - Bravo, Aura; Soytavanh, Mienmany; Philp, Joshua; Pazos, Mateo; Triana Ángel, Natalia; Otieno, Mary; Burkart, Stefan (2024)
Mixed Farming Systems (MFS) is one of the CGIAR research initiatives aimed at providing equitable and transformative pathways to improve the livelihoods of actors through sustainable intensification of crops and livestock across six countries. Cattle hold a key position within Laos’s development agenda in the project. This emphasis is driven not only by the significant shifts on livestock production across the region, marked by a transition from subsistence agriculture to commercialised and modernised agricultural systems, but also by the sector’s potential to integrate into regional Southeast Asia (SEA) growing markets, such as China and Vietnam, where demand for cattle products is rapidly increasing. Notably, Northen Laos has strong trade connections with the Chinese market and recently has signed international trade agreements that Laos hasn’t been able to meet for cattle commercialization (Mienmany, 2023).